Sexual Selection and Risk Taking : the Influence of Exposure to Potential Mates on Risky Decision Making - Weber, Kevin M. (My University, 2011)
This project assesses how exposure to potential mates affects risky decision making. This study exposed participants to a series of pictures of potential mates of either high attractiveness or average attractiveness; they were then instructed to rank-order the pictures based on both attractiveness and desirability.
Color poster with text, photographs, and graphs.
Keywords: Mate selection; Risk taking (Psychology)--Social aspects; Body image--Psychological aspects; Posters